Biodegradation of Microplastics: Mechanisms, Challenges, and Future Prospects for Environmental Remediation - Finayeva, Novlina; Kristanti, Risky Ayu; Rachana, Kong; Batubara, Ummi Mardhiah (Tecno Scientifica Publishing, 2025)
Microplastics are widespread environmental pollutants detected in aquatic, terrestrial, and atmospheric ecosystems. Their persistence, coupled with their potential to bioaccumulate and release toxic additives, raised serious concerns for both environmental and human health. This study aimed to assess microbial biodegradation as a viable strategy for reducing microplastic pollution. The research focused on the mechanisms through which microorganisms, particularly bacteria and fungi, degraded plastic polymers under various environmental conditions. Several microbial strains demonstrated the ability to degrade polymers such as polyethylene, polystyrene, and polyvinyl chloride, albeit at varying efficiencies. Environmental parameters such as temperature, pH, oxygen availability, and nutrient concentration, were found to significantly influence the rate and extent of microbial degradation. Despite these promising findings, the overall degradation rates observed in natural environments remained low. Moreover, challenges related to microbial specificity, metabolic limitations, and the scalability of degradation processes hindered the practical application of microbial treatments on a large scale. The complexity of polymer structures and the additives used in plastic manufacturing further complicated microbial breakdown. To overcome these barriers, future research should prioritize genetic engineering of microbial strains and the optimization of bioprocesses to improve degradation efficiency. Such advancements could pave the way for sustainable and effective biotechnological solutions to mitigate microplastic pollution.